Comparison of osteogenic potential of poly-ether-ether-ketone with titanium-coated poly-ether-ether-ketone and titanium-blended poly-ether-ether-ketone: An in vitro study - T Anjan Kumar; J Brintha Jei; B Muthukumar (Wolters Kluwer Medknow Publications, 2017)
Statement of Problem: Poly-ether-ether-ketone (PEEK), a high-performance semi-crystalline thermoplastic polymer, has been employed to replace the metallic implant components in orthopedics. There were various studies performed in accordance to medical grade PEEK, but the relationship between titanium dioxide (TiO2)-coated PEEK, TiO2-blended PEEK, and untreated PEEK still remains complicated, even undefined. Purpose: The purpose of this study was to compare and quantify the osteogenic potential of untreated PEEK, TiO2-coated PEEK and TiO2-blended PEEK. Materials and Methods: Three groups with ten samples in each group were designed for this study. They were Group 1 - Untreated PEEK, Group 2 - TiO2-coated PEEK, Group 3 - TiO2-blended PEEK. The PEEK samples were prepared according to the ISO standard 15309:2013 and milled to size of 15 mm × 2 mm, and the surfaces were finished with grit-blasted alumina of size 20 μm. In this 10 samples were chosen for Group 1. Group 2 samples were prepared by coating TiO2nanoparticles by arc ion plating, and Group 3 samples were prepared by blending TiO2nanoparticles in HAAKE rheocord with degree of blending analyzed by torque rheometer. These samples were tested for cytotoxicity using human osteosarcoma cells, and alkaline phosphatase (ALP) activity was performed to evaluate and quantify the bone mineralization process. The cross-sectional and the fracture morphology of coatings was observed by a field emission scanning electron microscope (SEM) with the magnification range ×20-×200,000. Result: Results of cytotoxicity assay and ALP assay of Group 1, Group 2, and Group 3 were statistically analyzed. SEM analysis result clearly showed the difference in the matrix before and after cell adhesion. Conclusion: The results made it evident that n-TiO2-coated PEEK was more versatile biomaterial of choice in implant dentistry followed by n-TiO2-blended PEEK and untreated PEEK.